2019
DOI: 10.1093/infdis/jiz626
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Laminin-Binding Protein Mediates Microbial-Endothelial Cell Interactions and Facilitates Dissemination of Lyme Disease Pathogens

Abstract: Borrelia burgdorferi conserved gene products BB0406 and BB0405, members of a common B. burgdorferi paralogous gene family, share 59% similarity. Although both gene products can function as potential porins, only BB0405 is essential for infection. Here we show that, despite sequence homology and coexpression from the same operon, both proteins differ in their membrane localization attributes, antibody accessibility, and immunogenicity in mice. BB0406 is required for spirochete survival in mammalian hosts, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In response to changing environmental conditions, B. burgdorferi replicates rapidly in the midgut during and following tick feeding, with the number of Borrelia increasing from <500 prior to feeding to about 1.7 x 10 5 per tick after 72 hours of feeding, a >300-fold increase (De Silva and Fikrig, 1995) (Ristow et al, 2015). BB0406, which like P66 potentially may serve as a porin and an adhesin, facilitates B. burgdorferi infection (Shrestha et al, 2017;Bista et al, 2020). Several nutrient salvage proteins required for survival in mammalian tissue have been identified (Table 1).…”
Section: Genes and Proteins Involved In Infection And Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In response to changing environmental conditions, B. burgdorferi replicates rapidly in the midgut during and following tick feeding, with the number of Borrelia increasing from <500 prior to feeding to about 1.7 x 10 5 per tick after 72 hours of feeding, a >300-fold increase (De Silva and Fikrig, 1995) (Ristow et al, 2015). BB0406, which like P66 potentially may serve as a porin and an adhesin, facilitates B. burgdorferi infection (Shrestha et al, 2017;Bista et al, 2020). Several nutrient salvage proteins required for survival in mammalian tissue have been identified (Table 1).…”
Section: Genes and Proteins Involved In Infection And Pathogenesismentioning
confidence: 99%
“…BB0406 is a recent addition to the group of lamininbinding adhesins as well as a putative porin (Shrestha et al, 2017;Bista et al, 2020). Mutants in bb0406 are infectious but attenuated in mice and show reduced bacterial burdens in tissues compared to the parental strain.…”
Section: Adhesins That Bind To Extracellular Matrix Componentsmentioning
confidence: 99%
“…2, 3B ). Candidate joint mediators identified previously by intravenous phage display, intravital microscopy and infectivity studies include Lmp1, BB0406, BB0347, OspC and VlsE, as well as P66, an integral membrane protein that mediates joint vascular transmigration but not EC surface interactions 3,16,25,41,42,44,45 . These candidates bind a wide range of host molecules that could potentially be involved in joint vascular interactions and dissemination, including glycosaminoglycans, laminin, fibronectin, plasminogen and integrins.…”
Section: Main Textmentioning
confidence: 99%
“…Although B. garinii DbpA/B has been found to support HUVEC interactions in flow chambers, B. burgdorferi N40 DbpA/B does not 46 , and the potential contributions of the B. burgdorferi B31 DbpA/B strain variant used in our studies to EC interactions and intravenous dissemination to skin have not been examined. Other candidates identified in intravenous infectivity studies are BB0406, P66 and the fibronectin-binding adhesin RevA 16,44 .…”
Section: Main Textmentioning
confidence: 99%
“…Once Lyme borreliae make the initial adherence contact with the endothelium they are able to transmigrate across the endothelium and reach the distant tissues (Moriarty et al., 2008; Norman et al., 2008). There are a few studies where it has been shown that Lyme borreliae are also able to transmigrate across the endothelial barrier of the brain microvasculature (Bista et al., 2020; Grab et al., 2005, 2009; Nyarko et al., 2006; Pulzova et al., 2011), while no studies have been published on the initial adhesion of Lyme borreliae to human brain microvascular endothelial cells (HBMECs).…”
Section: Introductionmentioning
confidence: 99%